1998
DOI: 10.1088/0031-8949/58/4/009
|View full text |Cite
|
Sign up to set email alerts
|

Collision Spectroscopy of Quartet and Doublet Transitions in doubly excited Ne7+

Abstract: We present the observation of VUV transitions between doubly excited states of Ne7+. Spectra were selectively produced by single electron capture in a cesium vapor by Ne8+ ions prepared in the metastable state 1s2s 3S by a previous collision of a Ne9+ beam with a gas target. The observed lines were assigned to 1s2l2l' → 1s2lnl'' and 1s2l3d → 1s2lnf electric dipole transitions. Furthermore, the forbidden electric quadrupole transition 1s2s2p 4Po-1s2p3d 4Fo has been identified at 78.71Å.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
(23 reference statements)
4
7
0
Order By: Relevance
“…Denis et al [20] previously observed Ne VIII 1s2s2p 4 P o -1s2s4d 4 D at 64.7 Å. We enhance the accuracy to 64.42 ± 0.03 Å, in agreement with the predicted value of 64.43 ± 0.09 Å.…”
Section: N = 2n = 4 Transitionssupporting
confidence: 91%
See 4 more Smart Citations
“…Denis et al [20] previously observed Ne VIII 1s2s2p 4 P o -1s2s4d 4 D at 64.7 Å. We enhance the accuracy to 64.42 ± 0.03 Å, in agreement with the predicted value of 64.43 ± 0.09 Å.…”
Section: N = 2n = 4 Transitionssupporting
confidence: 91%
“…Not only does the low transition probability preclude our observing this transition in our spectra, it is blended with strong lines coming from Ne VI 1s 2 2s2p 2 4 P -1s 2 2s2p4d 4 D o [32] and with an unknown line from Ne VII ions at 97.25 ± 0.02 Å which could come from a quintet transition [33]. Denis et al [20] observed this two-electron transition at 97.03 Å. This value does not correspond to the usual deviation from our SOCHFR calculations.…”
Section: N = 2n = 3 Transitionsmentioning
confidence: 71%
See 3 more Smart Citations